2020
DOI: 10.1057/s41260-020-00161-6
|View full text |Cite
|
Sign up to set email alerts
|

Gauging the effectiveness of sector rotation strategies: evidence from the USA and Europe

Abstract: This paper examines the performance of different sector rotation strategies for the U.S. and European market spanning the period 1999 to 2019. By utilising three different strategies we shed further light on the effectiveness of interest rate, momentum, & Fama-French 3 and 5 factor alphas as switching signals to enter and exit a particular sector. The emerging evidence suggests that within the European market, sector rotation strategies tend to produce returns above the average benchmark, both during contracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Positive conclusions on the advisability of applying the concept of sectoral rotation in investment portfolio management are presented in the works of Stangl et al [4], Wyatt and Kee [8] and in others. A research made by Alexiou and Tyagi [9] shows that the concept is still relevant, allowing investors to generate excess returns within the framework of the mature market. However, the implementation of the concept is characterized by significant diversity, and a fairly solid body of research is devoted to recommendations in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Positive conclusions on the advisability of applying the concept of sectoral rotation in investment portfolio management are presented in the works of Stangl et al [4], Wyatt and Kee [8] and in others. A research made by Alexiou and Tyagi [9] shows that the concept is still relevant, allowing investors to generate excess returns within the framework of the mature market. However, the implementation of the concept is characterized by significant diversity, and a fairly solid body of research is devoted to recommendations in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown the importance of the influence on the investment behaviour of a business exerted by such factors as stage of the organization's life cycle (Ivanov et al, 2018), type of economic activity (Alexiou & Tyagi, 2020), general level of corporate taxation (Steinmuller et al, 2019), company size (Zwick & Mahon, 2017). This means that tax incentives for investment should be based on differentiated instruments that take into account the business climate.…”
Section: Introductionmentioning
confidence: 99%